The SADC’s Infrastructure : A Regional Perspective - Ranganathan, Rupa; Foster, Vivien (2012)
Infrastructure improvements boosted growth in the Southern African Development Community (SADC) by 1.2 percentage points per capita per year during 1995-2005, mainly from access to mobile telephony. Road network improvements made small growth contributions, while power sector inadequacy had a negative impact. Infrastructure improvements that matched those of Mauritius, the regional leader, could boost regional growth performance by 3 percentage points. SADC's 15 member countries include small, isolated economies with island states, a mix of low- and middle-income countries, and larger countries with potentially large economies. The economic geography reinforces the importance of regional infrastructure development to create a larger market and greater economic opportunities. The region's infrastructure indicators are high for Africa. The regional road network is well-developed, and surface transport is comparatively cheap, but subject to delays and long-haul fees. An extensive railway system competes directly with road transport. With integration and improvements, SADC's ports could form an effective transshipment network. Air transport, dominated by South Africa, is the best in Africa. Electricity in southern Africa is well developed; the region leads Africa in generation capacity and low rates, but access is limited. ICT services are the most accessible among the regions, though expensive. Landlocked countries still need to be connected, and greater competition is needed to reduce costs. Completing and maintaining SADC's infrastructure will require $2.1 billion annually for a decade. For small countries, and large countries with small revenues, the burden may be insurmountable without external assistance.